MAPPING GLOBAL RESEARCH ON DIGITAL ACCOUNTING SYSTEMS FOR SMALL AND MEDIUM ENTERPRISES: A BIBLIOMETRIC ANALYSIS - Andi Candra, Yudas Tadius; Bambang Sutopo (Universitas Mercu Buana Yogyakarta, 2025)
This study aims to map and analyze global research trends on digital accounting systems within the context of Small and Medium Enterprises (SMEs) using a bibliometric approach. Data were retrieved from the Scopus database through a series of queries that combined terms related to digital accounting systems and SMEs, with filters applied for English-language articles published between 2015 and 2025. The identification and screening process followed the PRISMA protocol, yielding 129 articles that met the inclusion criteria. The collected bibliographic data were then analyzed using Biblioshiny to construct network maps of co-authorship, co-citation, and keyword co-occurrence. The results indicate a growing academic interest in digital accounting systems for SMEs, with several major thematic clusters related to the adoption and implementation of such systems, their impact on performance and financial information quality, as well as digital transformation and technological readiness of SMEs. While the field is rooted in accounting, information systems, and SME literature, research gaps remain, particularly concerning developing country contexts, the integration of emerging technologies, and user behavior. These findings provide a foundation for creating a future research agenda and offer guidance for policymakers and practitioners on promoting the more effective adoption of digital accounting systems among SMEs.